1986
DOI: 10.1002/tera.1420340111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin‐induced diabetes on fetal development of the rat

Abstract: The purpose of this study was to determine whether or not in rats with experimentally induced diabetes there is an increased frequency of congenital malformations; data in the literature are not consistent on this point. Virgin CD females rats were injected with 40-50 mg/kg streptozotocin (Stz) before mating (SIBM group) or on the first day of pregnancy (SI1). Both SIBM and SI1 females were divided into two groups according to their blood glucose levels: severely diabetic (SD, greater than 300 mg%) and mildly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
24
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 29 publications
8
24
0
1
Order By: Relevance
“…However, also under these drastic conditions, the effects on the embryos are indicative of developmental delay more than of a clear teratogenic effect. Similar findings have been shown by our previous experience with in vivo and in vitro experiments on diabetes [8,32,34,[46][47][48]. In this respect, a very interesting and deep critical review of the literature (144 references) has recently been published by Kalter [49], in which the author says: 'So far as the experiments are concerned, it is abundantly clear that the induction of diabetes by chemicals is often inefficient, and that, when induced, diabetes is frequently not teratogenic.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, also under these drastic conditions, the effects on the embryos are indicative of developmental delay more than of a clear teratogenic effect. Similar findings have been shown by our previous experience with in vivo and in vitro experiments on diabetes [8,32,34,[46][47][48]. In this respect, a very interesting and deep critical review of the literature (144 references) has recently been published by Kalter [49], in which the author says: 'So far as the experiments are concerned, it is abundantly clear that the induction of diabetes by chemicals is often inefficient, and that, when induced, diabetes is frequently not teratogenic.…”
Section: Discussionsupporting
confidence: 78%
“…Upon changing the strain of rats used in their experiments, this syndrome disappeared, showing a clear genetic predisposition in diabetes-induced malformations [6,7]. Apart from Eriksson's studies, the majority of experiments carried out on rats made diabetic with streptozotocin have not produced a significant increase in congenital malformations, and the major effect observed has been a developmental delay [8][9][10][11][12]. During the last decade, a number of studies have been carried out in vitro, using postimplantation mouse and rat embryos and rat serum as culture medium.…”
Section: Introductionmentioning
confidence: 98%
“…The hyperglycemic state has been shown to be associated with increased risk for embryonic dysmorphogenesis [28]. Increased incidence of malformations in the offspring of diabetic mothers with elevated HbA1c levels during early human pregnancy [29] and similar observations in rodent diabetic pregnancies [30][31][32] support these findings. Furthermore, since the time required for the induction of malformations is very short (24 h) in chick embryos as compared to mammalian embryos, e.g.…”
Section: Discussionmentioning
confidence: 67%
“…The underlying metabolic disorder may predispose offspring to develop metabolic diseases in later life (Silveira et al 2007). Several animal studies demonstrated a developmental delay for embryos recovered from diabetic mothers (Giavini et al 1986, Moley et al 1991. Our study provides new insights into the effects of a maternal DM during the preimplantation period by analyzing the AGE formation in both, the mother and the developing embryo.…”
Section: Discussionmentioning
confidence: 82%